Total Synthesis of Thiocladospolide A and Its C2-Epimer - Swami, Pramod; Mali, Maruti; Dhulshette, Baswaraj; Ghosh, Subhash (Synthesis, 2021)
The first total synthesis of the recently isolated natural product thiocladospolide A, along with its C2-epimer, is achieved in nine straightforward linear steps and 12% overall yield. The key feature of the synthesis is the construction of the macrocyclic ring via a late-stage ring-closing metathesis reaction followed by alkene reduction.
Keywords: total synthesis; macrolide; thiocladospolide A; sulfa-Michael addition; ring closing metathesis